POSSIBILITIES OF GYM IN ELEMENTARY EDUCATION IN GENERAL MUNICIPAL SCHOOL MUZAMBINHO-MG (Fiep Bulletin - online, 2014)
This study is part of the Extension Project General Gymnastics in Schools - GGES , the Center of Applied Sciences and Health Education - CeCAES and constitutes a qualitative research in order to verify the knowledge of students in the early years of elementary school on what is Physical Education - EF , Gymnastics and General Gymnastics - GG , in two local schools of Muzambinho - MG , Frei Florentino City School and City School Francisca Bianque . As instruments of data collection were used a questionnaire containing six open questions to check the students' knowledge of the EF . Gymnastics and GG . The sample consisted of 47 students ( 23 boys and 24 girls ) randomly selected , aged 7 and 9 years old , attending the 2nd and 3rd year of elementary school . The results indicate that students are building these concepts dynamically through their bodily experiences.
Keywords: Gymnastics; General Gymnastics; Physical Education